Analisis Efisiensi Teknis Usaha Tani Kentang di Provinsi Sumatera Utara dengan Pendekatan Stochastic Frontier Analysis - Ikhsanudin, Muhammad Rafi; Suhartini, Atik Mar'atis (Seminar Nasional Official Statistics, 2024)
Food security is a strategic element in the country's development. Potato as a leading horticultural crop is targeted to support food security. North Sumatera Province, as one of the largest potato producing regions in Indonesia, faces low productivity problem, even lower than Indonesia’s and other countries productivity value. High output without an increase in productivity indicates inefficiency problems. This study aims to analyse technical efficiency in North Sumatera Province using Stochastic Frontier Analysis and the data from Cost Structure of Horticulture Cultivation Household Survey 2018. The results show that technical inefficiency exists in potato production and all inputs positively influence output. In addition, farm households that operate with older, less educated farmers, no land ownership, no pest control, no business assistance, and no farmer group membership tend to be technically inefficient. Therefore, the stakeholders must cooperate to evaluate potato farming performance to achieve maximum production and productivity.